Photodynamic effect of methylene blue and toluidine blue on Streptococcus mutans and Candida albicans biofilm - Alanya-Ricalde, José Antonio (2021)
Objetive: To determine the photodynamic effect of methylene blue (MB) and toluidine blue (TBO) activated with therapeutic laser on Streptococcus mutans and Candida albicans biofilms. Material and methods: Sixty-one biofilm samples were analyzed in brain heart culture media (BHI) for 6 days, the samples were divided into 4 groups and immersed in: experimental group in 0.01% MB and 0.05% TBO, positive control group in 0.12% chlorhexidine gluconate (CHX) and negative control group in 0.9% sodium chloride (NaCl). The MB and TBO samples were irradiated with therapeutic laser with a wavelength of 660 nm, and 9 J/cm2 of power, each enamel block was in post-irradiation culture. The samples were cultured separately for the S. mutans and C. albicans strains, the method used was that of serial dilutions for the quantification of CFU after 5 days of culture. For the analysis, Student's T and Anova of one factor were used. Results: finding statistical differences between the four experimental groups in microbial growth (ANOVA p<0.05), in the analysis with the positive control group, there were no significant differences between MB versus S. mutans and C. albicans, in contrast to the TBO that showed significant differences (p<0.05). Conclusion: MB and TBO show in laboratory, a decrease in the growth of biofilm strains, TBO showed better effect in reducing the growth of S. mutans and C. albicans.